(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research presents a novel power battery management structure (BMS) specifically designed for electric vehicles (EVs). The BMS consists of various modules including a central control module, measurement and control module, battery pack, motor controller, direct-current motor, vehicle-mounted charger, current and electric quantity detection module, vehicle-mounted liquid crystal display module, switching group, memory module, clock module, and temperature management module